Coping strategies of females as victims of domestic violence: A literature review - Kusumawaty, Ira; Winta, Mulya Virgonita Iswindari; Pratiwi, Margaretha Maria Shinta (Institute of Computer Science (IOCS), 2024)
Coping strategies play an important role for women victims of violence in dealing with the psychological impact of violence. Their ability to develop effective strategies will influence their level of resilience and recovery. However, little research has directly examined this topic. It is important to understand the diverse coping strategies used so that intervention programs can strengthen adaptive coping for the long-term recovery process. This study aims to inventory the various coping strategies of women victims. This research utilized a literature review to review previous research. Scientific articles were searched from databases with the keywords ‘coping strategies’, ‘domestic violence’, ‘resilience’, and ‘female victims. From ten related literatures, a variety of coping strategies were found. While some were not adaptive, religious coping and social support increased long-term resilience. Intervention programs to strengthen constructive coping are needed.